57.4k views
1 vote
Algebraic Manipulation: Simplify 15x³ (y-z)² ÷ 10x⁻²(y²-z²)

Thank you!

User SouXin
by
5.2k points

1 Answer

5 votes

Answer:


=(3x^(5)(y-z))/(2(y+z))

Explanation:


(15x^3 (y-z)^2)/(10x^(-2)(y^2-z^2)) We need to solve this equation.

We know (x^2-y^2) = (x-y) (x+y)

Using the above formula, and taking 5 common:


=(3x^3 (y-z)^2)/(2x^(-2)(y^2-z^2))\\=(3x^(3+2) (y-z)^2)/(2(y^2-z^2))\\=(3x^(5) (y-z)(y-z))/(2(y-z)(y+z))\\=(3x^(5)(y-z))/(2(y+z))

User Guvante
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.